A PI3K p110α-selective inhibitor enhances the efficacy of anti-HER2/neu antibody therapy against breast cancer in mice. (4th May 2018) - Choi, Jae-Hyeog; Kim, Ki Hyang; Roh, Kug-Hwan; Jung, Hana; Lee, Anbok; Lee, Ji-Young; Song, Joo Yeon; Park, Seung Jae; Kim, Ilhwan; Lee, Won-Sik; Seo, Su-Kil; Choi, Il-Whan; et al.
ABSTRACT: Combination therapies with phosphoinositide 3-kinase (PI3K) inhibitors and trastuzumab (anti-human epidermal growth factor receptor [HER]2/neu antibody) are effective against HER2+ breast cancer. Isoform-selective PI3K inhibitors elicit anti-tumor immune responses that are distinct from those induced by inhibitors of class I PI3K isoforms (pan-PI3K inhibitors). The present study investigated the therapeutic effect and potential for stimulating anti-tumor immunity of combined therapy with an anti-HER2/neu antibody and pan-PI3K inhibitor (GDC-0941) or a PI3K p110α isoform-selective inhibitor (A66) in mouse models of breast cancer. The anti-neu antibody inhibited tumor growth and enhanced anti-tumor immunity in HER2/neu+ breast cancer TUBO models, whereas GDC-0941 or A66 alone did not. Anti-neu antibody and PI3K inhibitor synergistically promoted anti-tumor immunity by increasing functional T cell production. In the presence of the anti-neu antibody, A66 was more effective than GDC-0941 at increasing the fraction of CD4 +, CD8 +, and IFN-γ + CD8 + T cells in the tumor-infiltrating lymphocyte population. Detection of IFN-γ levels by enzyme-linked immunospot assay showed that the numbers of tumor-specific T cells against neu and non-neu tumor antigens were increased by combined PI3K inhibitor plus anti-neu antibody treatment, with A66 exhibiting more potent effects than GDC-0941. In a TUBO (neu+) and TUBO-P2J (neu−) mixed tumor model representing immunohistochemistry 2+ tumors, A66 suppressed tumor growth and prolonged survival to a greater extent than GDC-0941 when combined with anti-neu antibody. These results demonstrate that a PI3K p110α-isoform-selective inhibitor is an effective adjunct to trastuzumab in the treatment of HER2-positive breast cancer.